A critical review of key materials and issues in solid oxide cells. Issue 1 (6th January 2023) - He, Shuai; Zou, Yuanfeng; Chen, Kongfa; Jiang, San P.
Abstract: Solid oxide cells (SOCs) are all solid ceramic devices with the dual functionality of solid oxide fuel cells (SOFCs) to convert the chemical energy of fuels like H2, natural gas and other hydrocarbons to electricity and of solid oxide electrolysis cells (SOECs) to store renewable electric energy of sun and wind in hydrogen fuel. Among the electrochemical energy conversion and storage devices, SOCs are the most clean and efficient technology with unique dual functionality. Due to the high operation temperature (typically 600–800°C), SOCs exhibit many advantages over other energy conversion devices, such as low material cost, high efficiency and fuel flexibility. There has been rapid development of SOC technologies over the last decade with significant advantages and progress in key materials and a fundamental understanding of key issues such as an electrode, electrolyte, performance degradation, poisoning, and stack design. The reversible polarization also has a critical effect on the surface segregation and stability of the electrode and electrode/electrolyte interface. This critical review starts with a brief introduction, working principles and thermodynamics of SOC technology to readers with interests in this rapidly developing and emerging field. Then the key materials currently used in SOCs are summarized, followed by the discussion of the most advanced electrode modification methods and critical issues of SOCs, including the surface chemistry, segregation, electrode/electrolyte interface and varying material degradation mechanisms under reversible operations. The challenges and prospects of SOC technology for future developments are discussed. Abstract : The solid oxide cell (SOC) is the most efficient high‐temperature solid oxide devices for distributed electricity generation and hydrogen formation. This article updates and critically reviews the fundamental issues and development of key and high‐performance electrodes, electrolytes, and stack materials.